An automated computational tool to study MRI safety of implanted passive cardiovascular medical devices. (25th November 2020) - Baretta, A; Bursi, R; Palazzin, A; Emili, L
Abstract: Introduction: The absorption of radiofrequency (RF) energy during an MRI procedure may cause tissue heating in the vicinity of an implanted device, such as a stent or a stented valve, potentially causing patient harm. Computational modeling and simulation (M&S) can be used by medical device manufacturers to assess the RF-induced heating of implanted devices during an MRI scan and identify worst-case configurations within a given line of implants. However, despite the use of in-silico tools, a standard for in-silico testing of such problematic is still missing; The tool here proposed is a web-based application that automates the set-up and solution of RF-heating analysis, in line with existing standards for in-vitro testing. Methods: The presented tool is part of a commercial web-based platform. The tool was developed in collaboration with the market leader of computer-aided engineering software and as part of a Research Collaboration Agreement with the American regulatory body. Commercial software was used to compute RF energy absorption and thermal heating of implantable medical devices replicating the directives of the ASTM F2182–11a Standard Test Method. The model is integrated in an automated workflow. Each simulation submitted by the user is sent to the cloud infrastructure for solution. Simulation results are stored in a database for later retrieval and report generation. Results: The tool consists of a web-interface where the user can: i) upload the medical device computer-aided design (CAD) or select a simplified geometry from a library; ii) define the material properties of the device; ii) specify the desired input parameters specific to an MRI exposure scenario. Specifically, it is possible to study the device exposure: i) at different field frequencies (i.e., 64 MHz and 128 MHz); ii) at different powers (i.e., 2, 4 and 10 W/kg Whole body Specific Absorption Rate - SAR); iii) at different field polarizations (i.e., two circular and two linear); and iv) for different exposure time (i.e., form 240 s to 900 s). The presented tool allows the users to view and export results for each simulation, including electromagnetic fields, local SAR, and the temperature rise over time. Finally, the simulation results are summarized in an automatically generated report that follows regulatory guidance on M&S reporting. Conclusion: The presented web-based M&S tool allows users to perform the thermal safety assessment of implantable medical devices during an MRI procedure following established good simulation practices. Minimal training or background in computer modeling is required to use the tool. Specific potential applications of the tool include RF-heating assessment of cardiovascular devices (e.g., stents, stented valves, stent retrievers). The proposed platform promotes the broader adoption of digital evidence in preclinical trials for RF safety analysis, supporting the device submission process and pre-market regulatory evaluation. Funding Acknowledgement: Type of funding source: None